Cognitive Warfare, Disinformation, and Corporate Influence in Europe's Energy Transition: Information Control, Regulation, and Human Rights Implications - Marsili, M. (International Conference on Rethinking the Politics of Climate Change and Global Insecurities, 2026)
Europe’s green transition depends not only on the deployment of renewables and critical raw materials but also on shaping domestic and international narratives that underpin public support, investment flows, and geopolitical partnerships. This paper argues that ‘information control’ – the coordinated use of digital platforms, strategic communication, and cognitive-warfare techniques – is emerging as a decisive geoeconomic instrument in the global energy transition. Drawing on hybrid-warfare theory and human-rights frameworks, it examines how state and non-state actors deploy disinformation, algorithmic amplification, and platform design to advance or obstruct Europe’s regulatory ambitions (e.g. the European Green Deal). The paper maps key vectors of cognitive influence, including social-media campaigns on nuclear vs. renewables, deep-fake content undermining trust in battery–metal supply chains, and digital blockades of climate finance platforms. It then analyses case studies of hybrid-information operations attributed to China (promoting Belt and Road Initiative funded green infrastructure) and to Russia (sowing doubt over the European Union [EU] energy security). The study assesses the EU’s current defences – digital-literacy campaigns, transparency mandates, and the Digital Services Act – against the core principles of freedom of information and privacy. It concludes with policy recommendations for strengthening ‘cognitive resilience’, including embedding human-rights impact assessments and establishing an EU-level task force on energy-narrative security. This paper contributes a novel perspective by bridging geopolitics and geoeconomics through the lens of information operations, demonstrating that control over the digital ‘battlefield of ideas’ will shape Europe’s capacity to lead the global energy transition.